Velocity vector imaging echocardiography and NT‐proBNP study of fetal cardiac function in pregnancy‐induced maternal hypertension. Issue 5 (18th March 2019) - Yu, Li; Zhou, Qichang; Peng, Qinghai; Zeng, Shi; Yang, Zurong
Abstract: Purpose: To investigate whether acute and transient pressure overload in patients with pregnancy‐induced hypertension affects cardiac function in fetuses. Methods: We enrolled 104 singleton pregnant women with gestational ages ranging 30 to 33 weeks, visiting for prenatal care. Among them, 34 had gestational hypertension (GH), 32 had preeclampsia (PE), and 38 were healthy and formed the control group. Conventional echocardiographic and velocity vector imaging (VVI) variables were prospectively collected. Blood levels of N‐terminal pro‐brain natriuretic peptide (NT‐proBNP) were measured from cord blood drawn at birth. Results: The fetuses of mothers with preeclampsia had significantly lower left (LV) and right ventricle (RV) diastolic strain rate (SRd) and RV strain (S) and systolic strain rate (SRs) than controls. LV and RV S, SRd, and SRS were not different in fetuses of mothers with GH and controls. The NT‐proBNP levels were higher in fetuses of patients with PE than in GH and controls. Conclusions: In the third trimester of pregnancy, fetal biventricular function and NT‐proBNP levels are not significantly influenced by GH. Fetuses of mothers with PE present signs of LV and RV diastolic dysfunction, right ventricular systolic dysfunction, and elevated NT‐pro‐BNP levels. VVI echocardiography appears more sensitive than conventional echocardiography to evaluate fetal cardiac function.